PENDAMPINGAN KEGIATAN FISIK MOTORIK KASAR MENGGUNAKAN SIRKUIT DI LAHAN LEMBAGA PRASEKOLAH MINIMALIS KECAMATAN KARANGPLOSO MALANG - Ari Kusuma Sulyandari (LP2M Universitas Ibrahimy, 2020)
Focus of devotion was physical gross motor. In Karangploso there are 24% minimalist schools. So that it cannot perform motor physical activities optimally. The solution to that problem was to implemented a circuit. To help optimize the physical development of gross motor. Even though it was a minimalist school. After being given trained, teachers can design circuits in their schools. Material for safe circuits used for children. Material used can be stored. and used again.